2021
DOI: 10.3390/ijerph18031128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of External Load during Matches in Two Consecutive Seasons Using the Mediacoach® Video Analysis System in a Spanish Professional Soccer Team: Implications for Injury Prevention

Abstract: (1) Background: Knowledge of competition loads is a relevant aspect of injury prevention. We aimed to describe the training and match injury incidence and physical demand variables observed during a competition using a multi-camera video analysis system (Mediacoach®) (LaLigaTM, Madrid, Spain) in a professional Spanish soccer team during two consecutive seasons. (2) Methods: 30 players (age: 26.07 ± 3.78 years) participated in the study. Physical variables of 74 matches were collected retrospectively. Injury ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…Our findings suggest that the biomechanical characteristics of the movements required for individual sports may differ, the factors contributing to injury may differ, and the information required to provide injury prevention strategies may differ. This is similar to what was reported in the studies of Alcantarilla-Pedrosa, M. et al [ 52 ] and Demeco, A. et al [ 53 ]. Alcantarilla-Pedrosa, M. et al [ 52 ] showed in a video analysis of two seasons of a Spanish professional soccer team that due to the different positions (fullbacks, central-midfielders, central backs, wide-midfielders), the required motor characteristics differed, leading to different risk and severity of injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that the biomechanical characteristics of the movements required for individual sports may differ, the factors contributing to injury may differ, and the information required to provide injury prevention strategies may differ. This is similar to what was reported in the studies of Alcantarilla-Pedrosa, M. et al [ 52 ] and Demeco, A. et al [ 53 ]. Alcantarilla-Pedrosa, M. et al [ 52 ] showed in a video analysis of two seasons of a Spanish professional soccer team that due to the different positions (fullbacks, central-midfielders, central backs, wide-midfielders), the required motor characteristics differed, leading to different risk and severity of injury.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to what was reported in the studies of Alcantarilla-Pedrosa, M. et al [ 52 ] and Demeco, A. et al [ 53 ]. Alcantarilla-Pedrosa, M. et al [ 52 ] showed in a video analysis of two seasons of a Spanish professional soccer team that due to the different positions (fullbacks, central-midfielders, central backs, wide-midfielders), the required motor characteristics differed, leading to different risk and severity of injury. In a review study of padel, Demeco, A. et al also reported common injuries to their lower and upper extremities related to their change of direction movements and overhead strikes during the sport [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…We did not find an evolutionary tendency in players' physical responses over seasons. While some previous studies found an increase in high-intensity running and sprinting demands over consecutive seasons in the English Premier League 12 , 21 , the Spanish La Liga 22 , and in the Chinese Super League 23 , others reported few changes in physical parameters over consecutive seasons 24 . Interestingly, the studies that showed differences include data from seasons played up until 2013, while the most recent study 24 (including the current database) showed no increases in physical performance over the years.…”
Section: Discussionmentioning
confidence: 82%
“…These performances primarily vary according to the different playing positions of the players due to their different duties during the match [ 12 , 13 , 14 ]. For instance, as central midfielders (CMs) are responsible for the connection between defense and attack, these players generally achieve the greatest total distance.…”
Section: Introductionmentioning
confidence: 99%